Progression of targeted therapy in advanced cholangiocarcinoma - Huang, Yingying; Li, Xiaomei; Zhao, Yunbo (Chinese Journal of Cancer Research, 2015)
It is necessary to establish an effective therapy to improve the survival of patients with advanced cholangiocarcinoma (CCA). Recently, with the development of pathology research in CCA, a lot of special bio-markers such as EGFR, VEGF, HER2, and MEK et al. could be over expression or mutations in CCA patients. According to their changes, combinations of targeted therapy plus chemotherapy are now recognized as effective therapies for advanced CCA. The aim of this paper is to analyze recent promising studies about targeted therapy alone or combination with each other or with chemotherapies.